2015
DOI: 10.3109/09638288.2015.1066884
|View full text |Cite
|
Sign up to set email alerts
|

Does spirituality facilitate adjustment and resilience among individuals and families after SCI?

Abstract: Higher levels of spirituality were associated with improved quality of life, life satisfaction, mental health, and resilience for individuals affected by spinal cord injury. Health professionals can enhance the role that spirituality plays in spinal rehabilitation by incorporating the spiritual beliefs of individuals and their family members into assessment and intervention. By drawing upon meaning-making tools, such as narrative therapy, incorporating peer support, and assisting clients who report a decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 70 publications
2
31
0
4
Order By: Relevance
“…Overall, the methodological rigour of the qualitative studies identified in the review reflected many of the same limitations identified by Greenwood and colleagues (2019) in earlier qualitative studies investigating the experience of family caregivers after stroke. The findings with the quantitative studies that (i) there were no significant correlations between spirituality and other study variables (Teel et al, 2001) or (ii) significant findings of univariate association which disappeared once multivariate analyses were conducted (Qiu et al, 2008), was similar to findings for the review of spirituality studies after SCI (Jones et al, 2016). However, the employment of more robust measures of spirituality may help solve this issue.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Overall, the methodological rigour of the qualitative studies identified in the review reflected many of the same limitations identified by Greenwood and colleagues (2019) in earlier qualitative studies investigating the experience of family caregivers after stroke. The findings with the quantitative studies that (i) there were no significant correlations between spirituality and other study variables (Teel et al, 2001) or (ii) significant findings of univariate association which disappeared once multivariate analyses were conducted (Qiu et al, 2008), was similar to findings for the review of spirituality studies after SCI (Jones et al, 2016). However, the employment of more robust measures of spirituality may help solve this issue.…”
Section: Discussionsupporting
confidence: 61%
“…In the field of neurologic insult, initial studies that investigated the applicability of this research to the lives of family caregivers (after spinal cord injury (SCI) or traumatic brain injury (TBI)), found that spirituality had a protective (inverse) association to negative affect, depression and burden, and a positive association with positive affect (Jones et al, 2019;Simpson et al, 2020). These results reflect findings from studies among people with SCI or TBI which have found a positive association between spirituality and better life satisfaction, quality of life, and positive mental health (Jones et al, 2016;Jones et al, 2018). Given these results, is there a similar relationship between spirituality and caregiver outcomes after stroke?…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Such an experience can raise spiritual or existential questions [1] which may contribute to posttraumatic growth [2], or even posttraumatic struggle or decline [3][4][5]. Spirituality has been closely associated with increased levels of quality of life, life satisfaction and resilience among individuals with SCI [6][7][8][9][10][11], as well as lower levels of depression [12][13][14]. Furthermore, spirituality has often been identified as a key factor in adjustment after SCI [5,15,16].…”
Section: Introductionmentioning
confidence: 99%